Response of chickpea genotypes to drought stress under normal and late sown conditions - Yücel, Derya (AGRICULTURAL RESEARCH COMMUNICATION CENTRE, 2018)
Chickpea (Cicer arietinum L.) is one of the important legumes widely grown for dietary proteins in semi-arid Mediterranean climatic conditions. Thirty-four selected chickpea genotypes were tested under two (winter and late sowing) conditions to assess the genetic diversity for drought tolerance capacity. Factorial experiment in randomized complete block design with three replications was conducted during 2015 and 2016 at the Eastern Mediterranean Agriculture Research Institute Adana, Turkey. Significant differences and reduction was observed amongst the genotypes under stress condition compared to normal one. All traits except seed yield and hundred seed weight in 2015 were higher than those in 2016. Besides, all investigated traits significantly decreased in stress condition experiment compared to non-stress one in both years. It was observed that seven genotypes viz., ICC 1205, ILC 8617, ILC 4567, FLIP 03-21 C, FLIP 03-42 C, FLIP 01-24 C and ENA 8-2 genotypes provide early expressed early vegetative growth stages. Besides, Aksu, Arda, Cakir, Dikbas, EN 808, ENA 8-2, FLIP 03-108 C, ICC 1205 and Seckin had high seed yield under drought conditions during two years. Therefore, these genotypes can be used as donors of drought tolerance in future breeding program of chickpea.
Keywords: Chickpea; Drought; Growing conditions; Yield